COMPARISON OF BETA-HCG TITRATION AT BASELINE AND 4TH DAY AFTER SINGLE DOSE OF METHOTREXATE IN PATIENTS WITH ECTOPIC PREGNANCY IN PREDICTING THE SUCCESS OF PHARMACOTHERAPY: Life Sciences-Gynecology - TAYEBEH JAHED BOZORGAN; BEHNAZ AMIRNAZARI; MAHTAB MOTEVASELIAN; SARAH BAHRAMZADEH; MARAL BALESH (International Journal of Life Science and Pharma Research, 2022)
Recent studies have shown that ectopic pregnancy is a potentially life-threatening emergency, accounting for 1% of prevalence. Methotrexate is a folic acid antagonist used as an option for treating ectopic pregnancy. Considering that the drug also has significant side effects, this study tended to treat patients with single-dose regimens and compare beta-hCG titration at baseline and 4th day of receiving the drug in predicting the success or failure of pharmacotherapy. The population of this study included EP patients without rupture referring to the Mahdieh Hospital during 2010-2015. This study was designed as a cohort study. First, EP patients without rupture were enrolled in the study. Serum beta-HCG level was examined at baseline and 4th day in all patients treated by single dose methotrexate (50 mg/m2). T-test was used to compare parametric variables. To compare non-parametric variables in two groups, Mann-Whitney U test and Chisquare test were used and Fisher exact test was used, if necessary. Moreover, multi-variable regression analysis was used to predict hCG level for success. The results showed no significant difference in βhCG titration at baseline between two successful and unsuccessful groups in response to single dose methotrexate. There were interesting results in reducing βhCG titration between baseline and 4th day; this means that 81 (84%) out of 97 patients of the successful group had a decrease in βhCG level on the 4th day compared to baseline; therefore, single dose methotrexate was successful in 84% of patients with a 4th day beta drop. This study showed that βhCG level decreased on 4th day compared to baseline in 84% of patients who were successful in responding to a single dose methotrexate. However, βhCG level at baseline did not predict successful response to treatment.